Respuesta :

Answer:

x = -2 and y = 3

Step-by-step explanation:

It is given that,

4x + 5y = 7    -----(1)

3x – 2y = –12   ----(2)

To find the value of x and y

eq(1) * 3 ⇒

12x + 15y = 21   ----(3)

eq(2) * 4 ⇒

12x - 8y = -48  ---(4)

eq(3) - eq(4) ⇒

12x + 15y = 21   ----(3)

12x - 8y = -48 ---(4)

 0 + 23y = 69

y = 69/23 = 3

Substitute the value of y in eq(1)

4x + 5y = 7    ----(1)

4x + 5*3 = 7

4x = 7 - 15 = -8

x = -8/4 = -2

Therefore x = -2 and y = 3

Answer:

x = -2 and y = 3

Step-by-step explanation: